2021
DOI: 10.1149/1945-7111/abf5a7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Galvanic Corrosion Current between an Aluminum Alloy and Stainless-Steel Exposed to an Equilibrated Droplet Electrolyte

Abstract: Measurements of galvanic corrosion between UNS S13800 and UNS A97075 in bulk and equilibrated droplet electrolytes are compared with theoretical predictions of the corrosion current using calculations of the static diffusion-limited current, the classic Cottrell equation, and chemical reaction pathway models. The droplet electrolyte experiments use disks of stainless steel embedded in the aluminum alloy but isolated from electrical contact by an epoxy ring and connected via a zero-resistance ammeter potentiost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…During the salt spray test, a thin electrolyte solution layer, rich in O 2 from the atmosphere, is deposited continuously on the specimen surface. 89,90 A high diffusional flux of O 2 occurs through the thin solution layer due to the large concentration gradient. The solution layer also serves as a reservoir for reduction and oxidation reaction products.…”
Section: Discussionmentioning
confidence: 99%
“…During the salt spray test, a thin electrolyte solution layer, rich in O 2 from the atmosphere, is deposited continuously on the specimen surface. 89,90 A high diffusional flux of O 2 occurs through the thin solution layer due to the large concentration gradient. The solution layer also serves as a reservoir for reduction and oxidation reaction products.…”
Section: Discussionmentioning
confidence: 99%
“…Policastro et al investigated the galvanic corrosion current between an Al alloy and stainless steel through experimental and theoretical predictions to further the understanding of atmospheric corrosion at the interface of the metal system. [40] However, the two metals were not physically in contact with one another, but an insulating resin isolated them from one another so the galvanic corrosion current could be measured. Although authors concluded that the corrosion mechanism relied on the blocking of ion transport due to electrolyte chemical reactions to minimize further degradation, [40] the experimental setup lacks a depth of real in-use configuration.…”
Section: Analyzing Corrosion Product and Validating Corrosion Mechanismmentioning
confidence: 99%
“…[40] However, the two metals were not physically in contact with one another, but an insulating resin isolated them from one another so the galvanic corrosion current could be measured. Although authors concluded that the corrosion mechanism relied on the blocking of ion transport due to electrolyte chemical reactions to minimize further degradation, [40] the experimental setup lacks a depth of real in-use configuration. While in-use, dissimilar metals are often in physical contact with one another, and the local interfacial electrochemical and chemical changes that occur are critical in dictating corrosion mechanisms.…”
Section: Analyzing Corrosion Product and Validating Corrosion Mechanismmentioning
confidence: 99%
“…The galvanic corrosion behavior of Al alloys in highly concentrated chloride solutions, such as seawater, has been well documented; the entire Al alloy surface functions as the anode when Al alloys are coupled to steels [13][14][15][16][17] . Krüger and Mandel fabricated joined samples of Al alloy sheets and a zinc-coated steel rivet, and potentiodynamic polarization was performed in 5 mass% NaCl 13) .…”
Section: Introductionmentioning
confidence: 99%